An Empirical Analysis of Understanding Financial Statements in Islamic Education Institutions - Yunika Murdayanti*, Etty Gurendrawati, IGKA Ulupui, Mardi (International Journal of Advanced Science and Technology, 2020)
This study discusses emotional intelligence and interest in learning against understanding financial statements with spiritual intelligence as a moderating variable in Islamic educational institutions. This research is conducted and conclude, predict the implications of the facts of the weaknesses found, and provide findings. The method used in this study is a quantitative description by distributing questionnaires to respondents with research locations in the Islamic educational institutions in Jakarta and the data analysis method used is multiple regression analysis. The conclusions are the first hypothesis is rejected, which means higher emotional intelligence which of course will increase the understanding of financial statements, the second hypothesis is accepted learning planning that will improve understanding of financial statements, hypotheses that support strengths or weaknesses, the sophistication of spiritual intelligence and hypothesis received higher interest in learning and the higher the spiritual intelligence, the lower the understanding of financial statements. Suggestions are developing more independent variables and target respondents who can optimize financial reports in an Islamic educational institution.